Coding of multisensory temporal patterns in human superior temporal sulcus - Noesselt, Toemme; Bergmann, Daniel; Münte, Thomas F.; Heinze, Hans-Jochen; Spence, Charles (Frontiers in Integrative Neuroscience, 2012)
Philosophers, psychologists, and neuroscientists have long been interested in how the temporal aspects of perception are represented in the brain. In the present study, we investigated the neural basis of the temporal perception of synchrony/asynchrony for audiovisual speech stimuli using functional magnetic resonance imaging (fMRI). Subjects judged the temporal relation of (a)synchronous audiovisual speech streams, and indicated any changes in their perception of the stimuli over time. Differential hemodynamic responses for synchronous versus asynchronous stimuli were observed in the multisensory superior temporal sulcus complex (mSTS-c) and prefrontal cortex. Within mSTS-c we found adjacent regions expressing an enhanced BOLD-response to the different physical (a)synchrony conditions. These regions were further modulated by the subjects' perceptual state. By calculating the distances between the modulated regions within mSTS-c in single-subjects we demonstrate that the “auditory leading (AL)” and “visual leading (VL) areas” lie closer to “synchrony areas” than to each other. Moreover, analysis of interregional connectivity indicates a stronger functional connection between multisensory prefrontal cortex and mSTS-c during the perception of asynchrony. Taken together, these results therefore suggest the presence of distinct sub-regions within the human STS-c for the maintenance of temporal relations for audiovisual speech stimuli plus differential functional connectivity with prefrontal regions. The respective local activity in mSTS-c is dependent both upon the physical properties of the stimuli presented and upon the subjects' perception of (a)synchrony.